2021
DOI: 10.1002/stem.3356
|View full text |Cite
|
Sign up to set email alerts
|

ABCB5+ Dermal Mesenchymal Stromal Cells with Favorable Skin Homing and Local Immunomodulation for Recessive Dystrophic Epidermolysis Bullosa Treatment

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a rare, incurable blistering skin disease caused by biallelic mutations in type VII collagen (C7). Advancements in treatment of RDEB have come from harnessing the immunomodulatory potential of mesenchymal stem cells (MSCs). Although human bone marrow-derived MSC (BM-MSC) trials in RDEB demonstrate improvement in clinical severity, the mechanisms of MSC migration to and persistence in injured skin and their contributions to wound healing are not completely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Furthermore, beyond potential disease activity-related improvements, it might be anticipated that repeated doses given over a longer period of time could, by decreasing disease activity, reduce further damage accumulation. Interestingly, very recently it was shown that ABCB5 + MSCs possess a superior homing potential to injured tissues compared to bone marrow-derived MSCs, presumably due to increased HOXA3 gene expression, and are capable of secreting type VII collagen (76). Thus, it might be speculated that long-term treatment with ABCB5 + MSCs, beyond alleviating disease activity, could even enhance skin and mucosal structural integrity via accumulated deposition of type VII collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, beyond potential disease activity-related improvements, it might be anticipated that repeated doses given over a longer period of time could, by decreasing disease activity, reduce further damage accumulation. Interestingly, very recently it was shown that ABCB5 + MSCs possess a superior homing potential to injured tissues compared to bone marrow-derived MSCs, presumably due to increased HOXA3 gene expression, and are capable of secreting type VII collagen (76). Thus, it might be speculated that long-term treatment with ABCB5 + MSCs, beyond alleviating disease activity, could even enhance skin and mucosal structural integrity via accumulated deposition of type VII collagen.…”
Section: Discussionmentioning
confidence: 99%
“…A small subpopulation of mesodermal skin cells manifesting MSC features has been recently identified ( Riedl et al, 2021 ). These cells express the ATP-binding cassette subfamily B member 5 (ABCB5+ MSCs).…”
Section: Innovative Therapies For Diabetic Foot Ulcersmentioning
confidence: 99%
“…The improvement in adhesion has been attributed to either an increased expression of other junctional adhesion proteins or a reduction in inflammatory mediators that impair DEJ adhesion. Optimizing the number and frequency of MSC infusions, while addressing specific MSC subpopulations like skin homing ATP-binding or cassette subfamily B member 5 positive (ABCB5) MSC (Riedl et al, 2021) are currently being studied and designed to improve the outcome results. Injection of MSC-derived anti-inflammatory products carried in exosomes (Perdoni et al, 2014;Shabbir et al, 2015;McBride et al, 2018) is similarly under investigation, as are HMGB1 and SDF1 able to attract MSC.…”
Section: Cell Therapymentioning
confidence: 99%
“…If this pathway is defective, this predisposes to cancer. Only very few therapeutic possibilities are available for these diseases ( de Andrade et al, 2021 ) ( Weon and Glass, 2019 ). Screening of a library comprising Food and Drug Administration (FDA)-approved drugs has shown that the sulfonylureas acetohexamide and glimepiride are able in vitro to enhance viability in XPA cells after UV radiation at rather high dosages ( Mazouzi et al, 2017 ).…”
Section: Interfering With the Pathophysiological Pathways Disturbed By The Mutated Genementioning
confidence: 99%